Enforcing Reformation in Ireland and Scotland 1550 - 1700 (St. Andrews studies in Reformation history, 2006)
"By adopting an international perspective, the essays in this volume look at the motives, methods and impact of enforcing the Protestant Reformation in Ireland and Scotland. The juxtaposition of these two countries illuminates the similarities and differences of their social and political situations while qualifying many of the conclusions of recent historical work in each country."--BOOK JACKET.